KARAKTERISTIK PERAIRAN RAWA BANGKAU DAN KERAGAMAN IKAN DI KABUPATEN HULU SUNGAI SELATAN PROPINSI KALIMANTAN SELATAN - Rizmi Rizmi (Master Program of Environmental Science, Postgraduate Program of Udayana University)
This research aim to know kind of diversity of aquatic organisms and water quality of their habitat, that representate ecological condition of the waters, specially population dynamics of palustrine?s fishes in swamp Bangkau. Result of research indicate that condition of bio-physics and chemical quality of swamp Bangkau?s palustrine waters still be good enough relative, though by parsial there are parameter of quality of waters showing critical value like dissolved oxygen. But the condition quality of the waters represent specific quality of palustrine that found in South Kalimantan. Fishes sampling using rengge (gill-nets), pancing ( hand-line) and serok (hand-nets). Yields during observation amount to 16.368 individu, found 13 family and 26 species. Diversity Index value (H?) about 2,346 - 3,640. Eveness Index value range from 0,499 - 0,747 and Index Dominancy value show about 0,108 - 0,297. Station V show more environment suited for various species of fish from general till rareness species, causing variety species were founded with high value of Diversity index (H'), Eveness index (E) and Domination index (C).